A study on understanding consumers’ perception for buying Freedom sanitary napkin- a female hygiene product from ACI consumer brands - Leena, Ayesha Sirajee (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2016.